PEMBUKTIAN KEKUATAN HUBUNGAN ANTARA NILAI-NILAI PANCASILA DENGAN KEWARGANEGARAAN - Eko A Meinarno; Sri Fatmawati Fatmawati Mashoedi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
This study aimed to examine the relationship between the values of Pancasila in shaping a sense of citizenship in teenagers. Teenagers are the future residents of a nation that is expected to embody the values of Pancasila in public life. These values are inculcated through education at school, and could result in the creation of a sense of citizenship in teenagers. This study uses quantitative methods involving 297 high school students from the country, religious-affiliated schools and boarding school in West Java. Pearson correlation test showed a positive correlation and significant at all values of Pancasila and a sense of citizenship, which is the first principle, the second principle, third, fourth, and fifth. Thus, the higher the values of Pancasila individual then come high sense of citizenship. In particular, the strongest relationships arise from values of social justice and citizenship. http://dx.doi.org/10.17977/um019v1i12016p012